Use of Hospital Information System to Improve the Quality of Health Care from Clinical Staff Perspective: - Ebrahimpour Sadagheyani, Hassan; Mohammadpour, Ali; Mehdi Ghaemi, Mohammad; Darrudi, Reza (Galen Medical Journal, 2021)
Background: The development of hospital information systems (HISs) has a significant effect on care processes. In this regard, the clinical staff’s perspective is very important in evaluating the success of these systems. The present study aimed to evaluate the clinical staff’s perspective at hospitals affiliated to Neyshabur University of Medical Sciences on the effectiveness of the HIS in improving their performance and strategies for increasing the system effectiveness. Materials and Methods: In the present cross-sectional study, 120 clinical staff who actively worked with the HIS were included. A two-part questionnaire was used for data gathering. Results: From the perspective of the research population, the effective score of HIS was %64.42 in improving their performance, and %81.85 in the case of developed HIS according to the suggested strategies. According to the research scale, the effectiveness of the system could be improved from good to excellent in the case of implementation of strategies, so that there was a statistically significant difference between the pre- and post-effectiveness (P<0.001). Conclusion: Positive population perspective on the effectiveness of HIS in-performance improvement of the clinical staff indicated that there was a good context for the development and utilization of information technology in the hospitals. The clinical staff’s opinions and work needs as the primary group of patient care should be taken into consideration in order to increase the effectiveness of the HIS. [GMJ.2021;10:e1830]